PENGARUH DEBT DEFAULT, KUALITAS AUDIT, OPINI AUDIT TAHUN SEBELUMNYA, DAN AUDIT LAG TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Justita Dura; M Nuryatno (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This research aims at examining the effect of The Effect Of Debt Default, Quality Audit, Audit Opinion Preceding Years And Audit Lag To Audit Opinion Going Concern To Manufacture The Companies Listed In Bursa Efek Indonesia (BEI). It involves two variables is variable independen is Debt Default, Quality Audit, Audit Opinion Preceding Years And Audit Lag and variable dependen Audit Opinion Going Concern during 2007-2012. Based on judgement/purpose sampling 80 companies are considered being the sample in this study.The analysis shows primary featureof the result Debt Default and Audit Opinion Preceding Years have influence to Audit Opinion Going Concern and Quality Audit Audit Lag not have influence to Audit Opinion Going Concern.